Altitude, temperature, and malaria vectors in Nainital and Udham Singh Nagar districts of Uttarakhand, India: An evidence-based study - Ramesh C. Dhiman; Yogesh K. Yadav; Shweta Saraswat; Poonam Singh (Journal of Vector Borne Diseases, 2013)
Background & objectives: The relationship between altitude, temperature and malaria are poorly understood. Hence, a study was undertaken at three sites of Udham Singh Nagar (erstwhile Nainital district) and Nainital district (Uttarakhand) during 2010– 11 for the generation of evidences in the context of potential threat of climate change. Methods: Data on temperature and relative humidity (RH) were recorded through data-logger device in study villages at the altitudes of 166, 226 and 609 m were selected for detailed work. Mosquito collections were made fortnightly during 0600– 0800 hrs. Malaria incidence data were procured from concerned Primary Health Centres. Results: The study provides evidences of decrease in temperature with increase in altitude, even within a district resulting in variation in temporal distribution of malaria vector. With the increase of 67 m altitude between plains and foothill village, there was a reduction in temperature to the tune of 1.1°C and with further increase in altitude of 416 m between foothill and hilly villages, the temperature decreased by 0.27°C. The difference in temperature at three altitudes affects the Transmission windows (TWs) of both Plasmodium vivax (Pv) and P. falciparum (Pf), and opening of TWs are inversely proportional to altitude. In the plains, the TW for Pv and Pf were open for 11 and 10 months respectively, while 10 and 9 months in the foothills and 9 and 8 months, respectively for both the parasites at hilly altitude. Comparison of malaria vectors in plains, foothills, and hilly villages showed that the availability of Anopheles culicifacies and An. fluviatilis decreased with an increase in altitude from foothills to hilly areas. Interpretation & conclusion: This study may be extrapolated to know the suitability of occurrence of malaria vectors and transmission of parasites at different altitudes from the viewpoint of temperature as limiting factor in unknown areas.